2016
DOI: 10.1016/j.yfrne.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones and adult hippocampal neurogenesis: Regulation, implications, and potential mechanisms

Abstract: Neurogenesis within the adult hippocampus is modulated by endogenous and exogenous factors. Here, we review the role of sex hormones in the regulation of adult hippocampal neurogenesis in males and females. The review is framed around the potential functional implications of sex hormone regulation of adult hippocampal neurogenesis, with a focus on cognitive function and mood regulation, which may be related to sex differences in incidence and severity of dementia and depression. We present findings from precli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 360 publications
(442 reference statements)
3
113
0
1
Order By: Relevance
“…Sex differences in hippocampus are initiated during ontogeny through interaction of exposure to sex steroids and genotype (Arnold, ). Moreover, neurogenesis after birth, prominent in hippocampus (Clelland et al, ), and potentiated by puberty (Barha & Galea, ; Duarte‐Guterman, Yagi, Chow, & Galea, ; Mahmoud, Wainwright, & Galea, ), contributes to a larger adult hippocampal volume in females than males (Giedd et al, ). Further, healthy women have shown less age‐related decline in hippocampal volume than men (Pruessner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in hippocampus are initiated during ontogeny through interaction of exposure to sex steroids and genotype (Arnold, ). Moreover, neurogenesis after birth, prominent in hippocampus (Clelland et al, ), and potentiated by puberty (Barha & Galea, ; Duarte‐Guterman, Yagi, Chow, & Galea, ; Mahmoud, Wainwright, & Galea, ), contributes to a larger adult hippocampal volume in females than males (Giedd et al, ). Further, healthy women have shown less age‐related decline in hippocampal volume than men (Pruessner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol influences many types of learning and memory processes (Luine et al, 1998; Goodman et al, 2004; Leuner et al, 2004; Inagaki et al, 2010; Cover et al, 2014), and studies examining estradiol’s effects on neurogenesis, dendritic branching, and long-term potentiation have demonstrated that it can alter brain structure and function as well (Galvin and Ninan, 2014; Mahmoud et al, 2016; Srivastava et al, 2013). Given the higher prevalence of fear and anxiety disorders in women compared to men, a better understanding of how estradiol can affect the neural substrates and mechanisms that control fear responses is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, brain estrogen expression was reduced in adult female mice previously exposed to stress in adolescence but not in early adulthood which concludes that adolescent stresses suppress estrogen activities and interfere with its organizational actions to attain adult mating behavior. From these results, we can conclude that the individual's susceptibility to many neurodegenerative disorders including AD may be attained since early life and we may not be able to reverse it easily later [67,68].…”
Section: Brain Responses Variability To Sex Hormonesmentioning
confidence: 92%